PENGENDALIAN WERENG PUCUK METE (Sanurus indecora) TANAMAN JAMBU METE DENGAN CENDAWAN Synnematium sp. DI LABORATORIUM - Rahayu, Mallarangeng; Nurmas, Andi; Asniah, Asniah (Jurnal Agroteknos, 2011)
Pest is one of the constraints causing the decrease in the productivity of plants. One of the pests known as the most potential in causing the lost of cashew nut yield is Sanurus indecora. Generally, pest control still relies on the use of pesticides, while the other control methods such as biological control have not been applied optimally. The research of isolation, the effect of media and the use of Synnematium sp. to control S. indecora had been carried out from July to November, 2010. The objectives of this research were to know the pathogenic fungi infecting S. indecora in the field and the suitable media for their mass rearing, and to know the pathogenicity of Synnematium sp. on S. indecora. Test of the effects of media on the growth of Synnematium sp. consisted of five treatments and five replicates. Five kinds of media as treatment i.e: (1) PDA; (2) rice; (3) corn; (4) rice straw and (5) sago were arranged in complete randomized design. Test of the effects of spore concentrations of Synnematium sp. on mortality of S. indecora was conducted by using complete randomized design with five treatments and five replicates. Five concentrations of suspension as treatments were: control; 0.025 gml-1; 0.05 gml-1; 0.1 gml-1 and 0.2 gml-1. The results showed that the pathogenic fungus isolated from field infected S. indecora was Synnematium sp. The second experiment showed that the growth medium containing Rice Straw gave the best growth of Synnematium sp. colonies among the other treatments and 0.1 gml-1 of Synnematium sp. mycelium resulted in the highest mortality of S. indecora (57,5%) at 5 days after application. Key word: Cashew, Sanurus indecora, Synnematium sp.